Analisis Jual Beli Model Dropshipping Dalam Perspektif Etika Bisnis Islam - Yunita Rahmawati; Failasuf Muhammad Azka; Syamsul Bakri (Academica: Journal of Multidisciplinary Studies, 2022)
Dropshipping is an online business model in which there are buying and selling involving several parties such as buyers, suppliers and dropshippers. There are conveniences and benefits offered by the dropshipping business model. As in Islam, humans are allowed to seek wealth by doing business. However, the search for this wealth in a good way and in accordance with the Shari'a, one of which reflects the ethics of Islamic business ethics in it. The purpose of this study was to analyze the activities and strategies of the dropshipping model and the application of Islamic dropshipping business ethics. The method used is qualitative with the method of literature study. The results of the study show that the dropshipping model of buying and selling is permissible in Islamic business ethics as long as it does not violate Islamic values. Keywords: Buy and sell; Dropshipping; Islamic Business Ethics